Forever on the bay - McClain, Lee Tobin (McClain, Lee Tobin. Off season, 2022)
"Pleasant Shores cop Evan Stone has worked hard to become a man of his word, overcoming the alcoholism that sent him down the wrong path in his youth. So when his late best friend's sister asks for his help, he doesn't hesitate. He promised he'd watch out for Cassie, and the cottage next to his will be a perfect short-term refuge for her and her dog. The other half of that promise--to stay away from Cassie romantically--is harder to keep. Sheltered for years because of a childhood illness, Cassie is ready to reach for what she wants. And despite her family's warnings and her own fears, Cassie's heart wants Evan. As the return of his estranged son puts his sobriety to the test, Cassie and Evan are drawn together, finding strength through what they've each weathered. She knows Evan would risk anything to protect her, but are they willing to risk the price of loving, now and forever?" --